How negative institutional power moderates contestation: Explaining dissatisfied powers' strategies towards international institutions - Benjamin Daßler; Tim Heinkelmann-Wild; Andreas Kruck (The Review of International Organizations, 2024)
International institutions are increasingly under attack from their member states, who embark on varying and sometimes escalating modes of contestation. At the same time, states' negative institutional power, i.e. their opportunities to avoid undesired outcomes in international institutions, has been declining for some time. This paper claims that dissatisfied states' negative institutional power endowments are key to understanding their varying contestation modes: the more limited (extensive) the negative institutional power of dissatisfied states in an institution, the more radical (moderate) modes of institutional contestation they will choose. We argue that, all else equal, states' (1) inside options to prevent undesired outcomes within the institution and (2) their outside options to evade undesired outcomes by leaving the institution jointly condition whether they choose a strategy of voice , subversion , exit , or rollback to contest the dissatisfying institution. We assess the plausibility of our Negative Institutional Power Theory (NIPT) by means of four detailed case studies of the Trump Administration's contestation of the World Bank, the World Trade Organization, the Paris Agreement, and the Iran Nuclear Deal. We demonstrate the generalizability of our arguments by assessing our claims across eight additional instances of other dissatisfied powers' contesting different international institutions. The twelve case studies demonstrate that negative power matters for states' choice of institutional contestation modes. Our findings suggest that whether, in the future, international institutions will be increasingly challenged from within and outside, can be influenced by reforms that grant (or deny) states negative institutional power.
Keywords: F02; F13; F18; F33; F34; F51; F53; F55; 320; International institutions; Institutional power; Contestation; Veto power; Externalities